Strong time dependence of ocean acidification mitigation by atmospheric carbon dioxide removal - M. Hofmann (Nature Portfolio, 2019)
Carbon dioxide removal technologies are often touted as a potential strategy to combat ocean acidification. However, the authors show here that these strategies are only effective when included as part of aggressive and rapid climate-action, undermining the idea of geoengineering as a panacea.